Dimensions of performance to provide nursing services: a comparative analytical research in Baghdad of Rusafa Health Organization - حمود, سعد علي; حسين, قيس غميس (Journal of Economics and Administrative Sciences, 2015)
This research aims to study the performance of operations to provide nursing services, which included dimensions (quality, timeliness, leadership skills, behavioral manifestations, relationships with others, problem-solving and decision-making, job performance) and its effects in nursing performance. The research to prove the value of the performance of service delivery processes dimensions by nursing staffs working in Iraqi hospitals, nursing and measuring performance. To find out the nature of nursing services, and a comparison between hospitals to measure the extent of the application dimensional among themselves, and that by relying on the dimensions of a global study, which was measured on a sample of the Angels nursing working in hospitals, health Baghdad circle Rusafa, particularly in intensive care units, namely, (Hospital Ibn al-Nafis, Neurosciences Hospital, surgery nervous Hospital), and hit the sample (58) members, including nursing staffs in all functional levels.      It was a resolution the primary means of collecting information that adopted by the researcher, has been the subject of research included a set of intellectual questions that crystallized a whole research problem, and then determine its objectives and its importance, as well as the formulation of seven questions, and a quantitative measure to measure the performance of nursing. It was the use of a lot of statistical methods, such as (mean, standard deviation, and testing of moral arithmetic mean, and then compare it with the central premise, and through the test (T), as well as test analysis of variance table, and test analysis of variance table (LSD), to see the distinction between the two variables, and through the diagnosis and measurement of research variables, and test the effect relationships and the differences among them. was reached to a set of conclusions was the most important, the lack of significant differences between hospitals on the dimensions of operations differences.